WORKPLACE WELL-BEING TOWARDS WORK-FAMILY BALANCE OF FEMALE LECTURERS - Vera Nova; Safrilsyah Safrilsyah; Athiyyah Athiyyah; Salami Mahmud; Karjuniwati Karjuniwati (State Islamic University (UIN) Ar-Raniry, 2022)
Work-Family Balance is an important aspect that must be owned by teaching staff, including female lecturers. One of the factors that can affect work-family balance is workplace well-being. The purpose of this study was to determine the effect of workplace well-being towards the work-family balance on female lecturers at UIN Ar-Raniry Banda Aceh. This study used a quantitative approach with the regression method. The research instrument used was the work-family balance scale based on the theory of Greenhaus, Collins, and Shaw (2003) and the workplace well-being scale based on the theory of Paschoal and Tamayo (2008). The population in this study was 186 female lecturers with a research sample of 121 people selected based on a simple random sampling technique. Data analysis used a simple linear regression technique which showed the value of R = 0.392 with a significance value of p = 0.000 (p <0.05). This indicates that there is a very significant positive effect between workplace well-being on work-family balance of female lecturers at UIN Ar-Raniry Banda Aceh